Improving The Students’ Writing Skill By Using Discussion Learning Method At The Seventh Grade Of Mts Pab 1 Helvetia Medan - Tiara Safitri; Dwi Suci Amaniarsih (Journal MELT (Medium for English Language Teaching), 2022)
This study aims to determine the writing skills of seventh grade students at MTs PAB 1 Helvetia Medan. The formulation of the problem is: How does the application of discussion learning method to improve writing skills for the seventh grade students of Mts PAB 1 Helvetia Medan?. The purpose of this research was to know wheter the application of discussion learning method able to improve writing skill of the seventh grade students of Mts PAB 1 Helvetia Medan. The researcher applied the Classroom Action Research (CAR) method. The population in this study was the seventh grade students of MTs PAB 1 Helvetia Medan, totaling 32 students. Researchers obtained qualitative data and quantitative data, the results of the study showed an increase in students' writing skills through the discussion learning method, there were 84% who were able to do writing activities. These results come from data in cycle I and cycle II. In the pre-test there were 1 student who succeeded with a percentage of 3% and 31 students who did not succeed with a percentage of 97%, and in the first cycle there were 7 students who succeeded with a percentage of 22% and 25 students did not succeed with a percentage of 78% then in the second cycle there were 27 students who succeeded with a percentage of 84% and 5 students who did not succeed with a percentage of 16% in post-test II. After the treatment, their writing aspect improved significantly. It can be said that the discussion method is effective in improving students' writing skills.